Buddhist-Muslim Understanding on Protection of Life Through the Concepts of Buddhist Pāṇātipāta and Islamic Hifz al-Nafs: A Textual Analysis - Mohamed Ashath; Fathuma Afra; Nur Suriya Binti Mohd Nor (al-Afkar, Journal For Islamic Studies, 2024)
The academic study of the relationship between religion and the protection of life is inevitable hence most intolerance incidents occur in the name of religion or for the religion. In general, religions are concerned with human well-being whether they are followers of that religion or not. Although Buddhism and Islam contain detailed explanations of the protection of life uniquely, the meetings of Buddhists and Muslims are most often portrayed as violent confrontations in the Modern world. So, the objective of this paper is to analyze the concept of protection of life through the ideas of Pāṇātipāta from Buddhism and Hifz al-Nafs from Islam for interreligious understanding between Buddhists and Muslims. This research applies library-based qualitative methodology, in which the researchers use data that includes textual analysis of written materials such as books, journal articles, and internet sources. The findings disclose that although Buddhism and Islam differ fundamentally, both religions share a similar scope for the protection of life which prioritize humanity as the major measure. Hopefully, this study will be able to show that these two ideas are significant when dealing with religious intolerance make a better understanding among Buddhists and Muslims and pave the way for interreligious dialogue for peace and harmony.